2022
DOI: 10.1590/fst.00621
|View full text |Cite
|
Sign up to set email alerts
|

Use of products of vegetable origin and waste from hortofruticulture for alternative culture media

Abstract: Conventional culture media are expensive owing to their constituents. Thus, several studies have sought to develop and evaluate the efficacy of alternative, low-cost culture media, in most cases, using natural and easily accessible raw materials. The present study is a literature review, observing various formulations of culture media based on products of plant origin for the growth of microorganisms and production of microbial compounds of industrial interest. In most formulations, vegetable substrates, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…According to their efficacy and purpose, alternative culture media are divided into two groups: media for microbial growth and media for producing microbial compounds [ 20 ]. To better determine which group our vegetable waste-containing culture media fall into, the results of the microbial and chemical analyses of the culture broth containing KCW, CW, or OW of Lb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to their efficacy and purpose, alternative culture media are divided into two groups: media for microbial growth and media for producing microbial compounds [ 20 ]. To better determine which group our vegetable waste-containing culture media fall into, the results of the microbial and chemical analyses of the culture broth containing KCW, CW, or OW of Lb.…”
Section: Resultsmentioning
confidence: 99%
“…Using agricultural waste as a component of culture media has emerged as a circular economy strategy to cope with enormous amounts of waste. This waste can provide nutrients, including the organic carbon necessary for the growth of microorganisms [ 19 , 20 ]. Agro-industrial by-product wastes from fruit, brewing, and dairy industries have been investigated for their ability to improve the biological activity of LAB and produce bioactive compounds [ 21 - 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since food waste is reaching alarming levels nowadays, ways of reusing it have been continuously developed and improved. Actually, most of the agro-industrial waste and by-products have high nutritional composition such as complex carbohydrates, proteins, lipids, and many nutraceuticals [ 55 , 56 ]. Therefore, these residues represent a high potential to be valorized.…”
Section: 2-pe Production Via Fermentation On Agro-industrial Waste and By-productsmentioning
confidence: 99%
“…Application of plant-based media has many advantages over traditional media such as similarity to the natural habitat of microorganisms, helping to exploit low cost and available materials, making use of locally discarded materials, and environmentally friendly (Santos et al, 2022). Ibrahim et al (2020a) showed overexpression of activities such as indole acetic acid content and phosphate solubilizing activity of Streptomyces rochei DW3 and Kosakonia radicincitans DSM 16656 in plant-based media compared with traditional defined media.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Ibrahim et al (2020a) showed overexpression of activities such as indole acetic acid content and phosphate solubilizing activity of Streptomyces rochei DW3 and Kosakonia radicincitans DSM 16656 in plant-based media compared with traditional defined media. Also, according to Santos et al (2022), impediments are that natural media have not been studied in detail, evaluations on microorganism strains/species should be made prior to application. The source of plant materials is certainly also influenced by the production region as well as by the season and weather, which makes the quality unstable and heterogeneous.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%